Volition and control in law and in brain science: neurolegal translation of a foundational concept - Christensen, Julia F.; Rödiger, Caroline; Claydon, Lisa; Haggard, Patrick (Frontiers in Human Neuroscience, 2024)
The law assumes that healthy adults are generally responsible for their actions and have the ability to control their behaviour based on rational and moral principles. This contrasts with some recent neuroscientific accounts of action control. Nevertheless, both law and neuroscience acknowledge that strong emotions including fear and anger may "trigger" loss of normal voluntary control over action. Thus, "Loss of Control" is a partial defence for murder under English law, paralleling similar defences in other legal systems.Here we consider the neuroscientific evidence for such legal classifications of responsibility, particularly focussing on how emotional states modulate voluntary motor control and sense of agency. First, we investigate whether neuroscience could contribute an evidence-base for law in this area. Second, we consider the societal impact of some areas where legal thinking regarding responsibility for action diverges from neuroscientific evidence: should we be guided by normative legal traditions, or by modern understanding of brain functions? In addressing these objectives, we propose a translation exercise between neuroscientific and legal terms, which may assist future interdisciplinary research.